Redesign Of The Peanut Huller To Increase Productivity - Nugroho, Wahyu Adi Nugroho (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2022)
The health and safety of workers is very important, especially for home industries such as the peanut peeling industry. During work, workers feel soreness in the back, waist, arms, wrists and elbows. Therefore, it is necessary to do research on this matter. This study aims to increase productivity by redesigning the peanut peeler machine. In redesigning a work facility in the form of a peanut machine, things that need to be considered are the anthropometry of the operator's body size, complaints during work, the time of the peanut peeling process and heart rate during work. To determine the effect between the treatment before and after the design, a comparison test was conducted using the Paired Sample T-Test. The results showed that the standard time in the conditions before the design was 0.102 hours/kg and the standard output was 29.5 kg/hour. Meanwhile, after the design of 0.023 hours/kg and the standard output is 130.5 kg/hour with an increase in standard output of 101 kg/hour. Energy consumption after working in conditions before design is 4.58 Kcal/minute and after design is 3.7 Kcal/minute with a decrease in energy consumption level of 0.88 Kcal/minute.